The diatom Fragilariopsis cylindrus: A model alga to understand cold‐adapted life. Issue 2 (30th March 2023) - Otte, Antonia; Winder, Johanna C.; Deng, Longji; Schmutz, Jeremy; Jenkins, Jerry; Grigoriev, Igor V.; Hopes, Amanda; Mock, Thomas
Abstract: Diatoms are significant primary producers especially in cold, turbulent, and nutrient‐rich surface oceans. Hence, they are abundant in polar oceans, but also underpin most of the polar food webs and related biogeochemical cycles. The cold‐adapted pennate diatom Fragilariopsis cylindrus is considered a keystone species in polar oceans and sea ice because it can thrive under different environmental conditions if temperatures are low. In this perspective paper, we provide insights into the latest molecular work that has been done on F. cylindrus and discuss its role as a model alga to understand cold‐adapted life.